Future Generation’ Mobile Protection and Security - Bari, MA; Sultana, I; Fathima, N; Ahamad, S (International Journal of Computer Sciences and Engineering, 2025)
The future of mobile wireless communication networks will be experiencing several generations. This kind of development will drive the researches of information technology in industrial area of continuous development and evolution. In this paper, we have explored future generations of mobile wireless communication networks including 4th, 5th，and so forth. If looking to past, wireless access technologies have been followed different evolutionary paths with aim at unified target related to performance and efficiency in high mobile environment. Android develops one of the most popular mobile operating system in the whole world, as a side effect of this popularity, Android becomes the most preferred destination of hackers with different aims, some of them looking for making money and others are just having fun by raid the privacy of the others without their authorization. Nowadays, Android security has become a major problem because of the free application provided and functionalities that make it very easy for anyone to progress it. However, various systems have been planned by a large number of scholars to address these problems.